Answer :

Answer:

m = - 2.27 or m = 16.27

Step-by-step explanation:

Given

m² - 14m - 37 = 0 ( add 37 to both sides )

m² - 14m = 37

To complete the square

add ( half the coefficient of the m- term )² to both sides

m² + 2(- 7)m + 49 = 37 + 49, that is

(m - 7)² = 86 ( take the square root of both sides )

m - 7 = ± [tex]\sqrt{86}[/tex] ( add 7 to both sides )

m = 7 ± [tex]\sqrt{86}[/tex], that is

m = 7 - [tex]\sqrt{86}[/tex] ≈ - 2.27 or m = 7 + [tex]\sqrt{86}[/tex] ≈ 16.27

Other Questions